2020
DOI: 10.1136/bmjopen-2020-042800
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of workplace violence towards health workers in a Chinese hospital: a cross-sectional study

Abstract: ObjectiveThis study aimed to assess the risk factors associated with workplace violence towards health workers (HWs) in a Chinese hospital.MethodsWe conducted a cross-sectional survey in a Chinese secondary hospital in 2019 using an international survey questionnaire, and collected valid data from 1028 HW respondents via mobile phone. Alongside analysing the potential association between exposure to violence and respondents’ characteristics, we compared the workplace violence between this survey and a baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…We also found that most perpetrators were patients' relatives, further confirming previous research (26). We believe that this is caused by a lack of empathy of patients' relatives toward the doctor.…”
Section: Analysis Of the Characteristics Of Perpetratorssupporting
confidence: 89%
See 2 more Smart Citations
“…We also found that most perpetrators were patients' relatives, further confirming previous research (26). We believe that this is caused by a lack of empathy of patients' relatives toward the doctor.…”
Section: Analysis Of the Characteristics Of Perpetratorssupporting
confidence: 89%
“…The characteristics of hospital violence events found in this study are consistent with those of previous studies. Most of these cases occurred in secondary hospitals, outpatient departments, and emergency departments (25,26). Moreover, most perpetrators committed violence by placing wreaths, blocking doors, burning papers, placed the corpse, and physically assaulting others (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relates to a previous study, when the staff was either preparing for or providing health services (43). This corresponded to the ndings of a study in Hong Kong and China (16,41,44). The third factor was the last factor of our logistics model.…”
Section: Associated Factors and Wpvsupporting
confidence: 53%
“…18 The Law on Basic Health Care and Health Promotion was also implemented as the country's first basic and comprehensive healthcare law. 19 Primary doctors and nurses will be encouraged to participate in more health promotion tasks in their daily work. 17 It is meaningful to evaluate the current status of health promotion among healthcare professionals in the new era in China, and to provide suggestions to improve their ability.…”
Section: Introductionmentioning
confidence: 99%